The correlation analysis between training and attitudes towards building information modelling (BIM) adoption in Malaysian construction industry / Dr. Har Einur Azrin Baharuddin and Airul Faizal Othman - Baharuddin, Har Einur Azrin; Othman, Airul Faizal (College of Built Environment, 2023)
The adoption of Building Information Modelling (BIM) as a technological advancement in the industry has become a main concern among its stakeholders.